Study on the Efficient Methods for Chicken Eggshell windowing and the Factors Affecting the Hatchability - Yan,HF (2020)
ABSTRACT In order to find out the main factors influenced the hatchability and improve the hatchability of the windowed chicken eggs at stage X, several experiments were made on the basis of the former patent of eggshell windowing methods on equatorial plane, such as cutting and sealing techniques, air cell recovering, laying position immediately after sealing, as well as the injection volumes into the subgerminal cavity of the blastoderm. The result showed that:1) the best sealing material combination was straw powder (SP) and instant glue (IG); 2) there was a highly positive correlation between air cell rate and hatchability; 3) the highest hatchability increased to 71.6% when the eggs were windowed and sealed with IG dropped firstly and then SP sprinkled, finally lay down with the blunt end upward immediately after being sealed; 4) the hatchability was significantly reduced as injection volume (DMEM) was increased (p<0.05 or p<0.01) from 1 µL to 10 1 µL, and the group of injecting 1 µL was the highest (48.4 %). The hatchability and efficiency with such method of windowing, injecting, and sealing was the highest at the present time (more than 30 eggs per hour per person), and it might be broadly used in the fields of avian transgenesis, genetic resources preservation, and embryonic development model of human medicine.